2010
DOI: 10.1155/2010/364290
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glucose and Glutamine Lymphocyte Metabolisms Induced by Type I Interferon α

Abstract: In lymphocytes (LY), the well-documented antiproliferative effects of IFN-α are associated with inhibition of protein synthesis, decreased amino acid incorporation, and cell cycle arrest. However, the effects of this cytokine on the metabolism of glucose and glutamine in these cells have not been well investigated. Thus, mesenteric and spleen LY of male Wistar rats were cultured in the presence or absence of IFN-α, and the changes on glucose and glutamine metabolisms were investigated. The reduced proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…In contrast, our studies reflect a scenario of localized virus infection where cells in close proximity experience high concentrations of IFN-␣/␤ produced by tissue-resident cells or plasmacytoid dendritic cells during an acute immune response to virus infection. In other studies, Navarro et al examined the effects of type I IFN treatment on glucose metabolism in primary mesenteric and splenic lymphocytes after 48 h and likewise showed a suppression of glucose uptake (72). Notably, in the earliest IFN experiments of Isaacs and Lindenmann, conducted in chicken embryo cells, they identified a modest IFN-inducible effect on lactate production after 4 h, an indicator of glycolysis (73).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our studies reflect a scenario of localized virus infection where cells in close proximity experience high concentrations of IFN-␣/␤ produced by tissue-resident cells or plasmacytoid dendritic cells during an acute immune response to virus infection. In other studies, Navarro et al examined the effects of type I IFN treatment on glucose metabolism in primary mesenteric and splenic lymphocytes after 48 h and likewise showed a suppression of glucose uptake (72). Notably, in the earliest IFN experiments of Isaacs and Lindenmann, conducted in chicken embryo cells, they identified a modest IFN-inducible effect on lactate production after 4 h, an indicator of glycolysis (73).…”
Section: Discussionmentioning
confidence: 99%
“…In exhaustion, however, T cells have reduced production of IL-2, and this may contribute to reduced glucose metabolism of exhausted T cells (103). Navarro et al (111) demonstrated that, unlike IL-2, the antiviral cytokine type I IFN member IFN- α diminished glucose and glutamine metabolism in activated lymphocytes. This defect was characterized by decreased activity of the metabolic enzymes glucose-6-phosphate dehydrogenase (G6PDH), citrate synthase, and phosphate-dependent glutaminase.…”
Section: T Cell Dysfunction and Metabolism In Anergy And Exhaustionmentioning
confidence: 99%
“…33 Persistent activation of macrophages by neoplastic cells does not favor sustained antitumor T-cell responses. [34][35][36][37][38] This may be exacerbated by IFN-c-associated with Treg reprogramming, which specifically polarizes tumor-associated macrophages into an M1 pro-inflammatory phenotype. 39,40 This is characterized by increased synthesis of IL-6, production of reactive oxygen species (ROS), specific changes of glucose metabolism and a capacity to modulate iron metabolism.…”
Section: Role Of Macrophage Activation With Treg Reprogrammingmentioning
confidence: 99%
“…Several in vivo and in vitro experimental models involving Treg reprogramming into IFN‐ γ ‐producing cells, have shown that loss of Treg cell activity is accompanied by pro‐inflammatory polarization of peritoneal macrophages with associated release of pro‐inflammatory and immunosuppressive cytokines . Persistent activation of macrophages by neoplastic cells does not favor sustained anti‐tumor T‐cell responses . This may be exacerbated by IFN‐ γ ‐associated with Treg reprogramming, which specifically polarizes tumor‐associated macrophages into an M1 pro‐inflammatory phenotype .…”
Section: Role Of Macrophage Activation With Treg Reprogrammingmentioning
confidence: 99%